One step pre-hardening micropropagation of Bambusa balcooa Roxb. - Bharat Gami, Nisha Patel, Vipul Bariya., Beena Patel (Journal of Phytology, 2015)
Bambooâ€™s fast growth and ability to sequester atmospheric carbon consequently mitigate climate change.Abellonâ€™s mission is to reduce CO2 from the environment by growing bamboo on marginal land and using this biomass for bioenergy. Bambusa balcooa Roxb. micropropagation protocol is established for a consistent supplyÂ of quality plantlets. Surface sterilization of nodal explants using 0.1% mercuric chloride followed by initiation in liquid and solid media with and without Gentamycin (3.0-8.0 mg/L) containing Murashige and Skoog (MS)Â media supplemented with 0.01% myo-inositol, 3% sugar, 25 mg/L citrate 50 mg/L ascorbate, and 3.5 mg/L 6-benzylaminopurine (BAP) as growth regulator. Shoots were multiplied using MS medium augmented with 3%Â sugar, 6% agar, 0.01% myo-inositol with 3 mg/L BAP and 0.5 mg/L naphthalene acetic acid (NAA). Shoot clusters were rooted in MS supplemented with 4 mg/L NAA, pre-hardened in half MS, acclimatized using coco peat, andÂ vermicompost while at net house using vermicompost, soil, sand, and vesicular arbuscular mycorrhiza (VAM) culture. 97% bud break was achieved from initiation while overall success ratio for establishment was 85%.Â Sub-culturing shoots showed proliferation rate of 3.5-fold. Rooting was successfully achieved with 83% rate.Acclimatization rate at primary and secondary hardening was 72%. The uniqueness of the study lies as bambooÂ confines to tropical region, however; we have described B. balcooa mass multiplication protocol using explantsÂ from arid region with one step pre-hardening process. The protocol achieved multiplication rate of 3.5-fold, overallÂ survival rate 74.66% using vermicompost and VAM for acclimatization of B. balcooa.